Extracapsular extension and tumor implants in lymph nodes with canine mammary carcinoma metastasis: Study of the impact on survival. (October 2021) - Gonçalves, A.D.B.B.; de Pinho, T.C. Reis; Toledo, F.A.O.; Balabram, D.; Ferreira, E.; Campos, M.R.A.; Cassali, G.D.
Abstract: Regional lymph node status impacts survival in dogs with malignant mammary tumors. However, few studies have evaluated extracapsular extension and tumor implants in regional lymph node metastases in dogs with mammary carcinoma. Therefore, 84 cases of mammary carcinomas with metastases in inguinal and/or axillary lymph nodes from female dogs of different breeds and a total of 139 metastatic lymph nodes were evaluated by routine histological staining. Clinical and pathological characteristics of primary tumors as well as the presence of extracapsular extension and tumor implants in the lymph nodes were analyzed, in addition to survival. One to 5 lymph nodes were evaluated in each case. Extracapsular extension and tumor implants were present in 17.9% and 39.3% of cases, respectively. The simultaneous presence of extracapsular extension and tumor implants were associated with an increased risk of death (hazard ratio 10.46). In addition, "special type carcinomas", high histological grade (grade III), and presence of extracapsular extension associated with tumor implants were related to a worse prognosis and shorter survival times ( p < 0.05). Based on these results, we highlight the importance of identifying extracapsular extension and tumor implants in dogs with metastatic mammary carcinomas, as they are associated with a higher risk of death and shorter survival. Highlights: Extracapsular extension (ECE) was present in 17.9% of lymph node metastasis of mammary carcinoma. Tumor implants (TI) were present in 39.3% of lymph node metastasis of mammary carcinoma. ECE and TI simultaneously present had a hazard ratio of death of 10.46 in comparison to lymph node metastasis only. The presence of ECE in lymph node metastasis of mammary carcinomas was associated with shorter survival times.